2021
DOI: 10.3390/su13063042
|View full text |Cite
|
Sign up to set email alerts
|

Government Effectiveness and the COVID-19 Pandemic

Abstract: The COVID-19 pandemic threatens to derail progress achieved in sustainable development. This study investigates the effectiveness of government policy responses to the COVID-19 pandemic, namely the number of deaths. Using the Oxford COVID-19 Government Response Tracker (OxCGRT) dataset for a global sample of countries between March and September 2020, we find a non-linear association between government response indices and the number of deaths. Less stringent interventions increase the number of deaths, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 17 publications
3
40
0
1
Order By: Relevance
“…Similarly, WHO indicated that outdoor gatherings are safer than indoor ones, particularly if indoor spaces are small and without outdoor air coming in 6 . Our result is similar to Chisadza, Clance [32] findings, which indicated that the strictest government response measures are associated with more COVID-19 deaths.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, WHO indicated that outdoor gatherings are safer than indoor ones, particularly if indoor spaces are small and without outdoor air coming in 6 . Our result is similar to Chisadza, Clance [32] findings, which indicated that the strictest government response measures are associated with more COVID-19 deaths.…”
Section: Resultssupporting
confidence: 90%
“…One strand of the literature suggests that the government policy response measures have effectively reduced the number of COVID-19 cases [20] . Contrarily, others argue that strict government response measures could increase the number of COVID-19 cases and death because of the severe economic implications of the measures [ 18 , 32 ]. The empirical findings on the impact of the government policy response on the spread of the COVID have been contradictory.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Robust evidence now shows that, under most conditions, early adoption of stringent NPIs is associated with a reduction in transmission [16][17][18][19][20][21][22][23][24][25][26][27]. However, with full vaccination still elusive, and with the possibility of vaccine-escaping variants emerging, NPIs can be expected to continue playing a significant role in managing the pandemic in the foreseeable future [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The study emphasizes the need to reboot the state policy in the field of regional development management. Chisadza et al (2021) discuss the effectiveness of public administration during the pandemic and assess the efficiency of the tools for limiting the spread of the disease in different countries and regions. It was found that the correlation between the severity of anti-COVID measures and the decrease in the incidence rate is not al-динамика уровня безработицы и доходов населения в разрезе федеральных округов и регионов Российской Федерации.…”
Section: Theoretical Frameworkmentioning
confidence: 99%